Resonating Culture: Ethnomusicological Theories Unveiling Zhuhu Music in Yangxin Tea-picking Opera of China - Chengyao, Duan; Abdullah, Mohd Hassan (Universitas Negeri Medan, 2024)
More than a century ago, the enchanting tea-picking songs enjoyed widespread popularity among the residents of Yangxin in China. These songs served as a source of entertainment within the tea plantation quarters. Folk music artists subsequently reworked these melodies, transforming them into short tunes for collective singing and dancing during the Lantern Festival. The integration of Huangmei tea-picking opera with the